Preprocedural Checklist for Magnetic Resonance Imaging Patients Undergoing General Anesthesia: A Process Improvement Plan to Enhance Reimbursement. Issue 3 (July 2018) - Hartl, Susan; Rice, Andi N.; Gupta, Dhanesh K.; Goode, Victoria
Abstract : Thorough documentation is essential for hospital reimbursement from payors such as the Centers for Medicare & Medicaid Services. Inconsistencies and incomplete documentation can occur if workflow is not standardized especially in cases with interdisciplinary involvement. Documentation for patients undergoing magnetic resonance imaging (MRI) with anesthesia services was examined and revealed an opportunity for improvement to avoid financial losses. A preprocedure checklist to improve documentation and standardize workflow was implemented. We compared documentation from preintervention MRI to postintervention MRI with anesthesia services. Documentation that met the reimbursement requirements increased from 5% in the preintervention group to 90% in the postintervention group after the preprocedural checklist implementation. A cost estimate showed a reduction in potential revenue loss from preimplementation to postimplementation groups. The standardization of workflow with the aid of checklists helped meet the documentation requirements for adequate reimbursements and reduced the risk of potential reimbursement losses from payors.